Assessment of the immunotoxic potential of trichloroethylene and perchloroethylene in rats following inhalation exposure. (September 2013) - Boverhof, Darrell R.; Krieger, Shannon M.; Hotchkiss, Jon A.; Stebbins, Kenneth E.; Thomas, Johnson; Woolhiser, Michael R.
<x xml:space="preserve">Abstract</x> The immunotoxic potential of trichloroethylene (TCE) and perchloroethylene (PERC) was assessed after inhalation exposure through the evaluation of the antibody forming cell (AFC) response to sheep red blood cells (SRBC). Female Sprague-Dawley rats were exposed to TCE or PERC vapor at 0, 100, 300, or 1000 ppm for 6 h/day, 5 days/week for 4 weeks (20 exposure days). Additional 0 ppm control groups were included and were dosed with cyclophosphamide via intraperitoneal injection to serve as positive immunosuppressive controls in the SRBC assay. Additional end-points evaluated included liver, kidney, spleen, and thymus weights, hematology, cellular differentials in bronchoalveolar lavage fluid, histopathology of select tissues, and assessment of the phagocytic activity of pulmonary alveolar macrophage (PERC only). Exposure to the high concentration of TCE (1000 ppm) resulted in increases in relative liver and kidney weights and suppression of AFC responses (AFC/spleen and AFC/106 spleen cells) by ≈ 70%, while no treatment-related effects were noted at 100 and 300 ppm. Animals exposed to PERC at levels of 300 or 1000 ppm had statistically significant increases in relative liver weights that were accompanied by very slight hypertrophy of the centrilobular hepatocytes. Animals exposed to PERC did not demonstrate a treatment-related effect on the AFC response and no effect was noted on the phagocytic activity of pulmonary alveolar macrophages. The results of these studies indicate that TCE had immunotoxic potential only at high exposure concentrations (1000 ppm), while PERC, at similar exposure concentrations, did not display any evidence of immunotoxicity.